Torysi, czy wigowie? Problem relacji konserwatyzmu i liberalizmu w brytyjskiej tradycji politycznej - Piotrowski, Przemysław (Wydawnictwo Uniwersytetu Rzeszowskiego, 2013)
Liberal conservatism was often able to consolidate leadership. This is demonstrated by the governments of R. Peel and M. Thatcher. However, these same figures indicate that combining liberalism with conservatism at times also caused political conflicts and disputes in the Tory party. Thatcherism can be identified in the overwhelming opposition to the paternalistic tradition of post-war governments of W. Churchill, H. Macmillan and E. Heath, but according to some commentators, there is an important continuity between them, which does not invalidate the libertarian rhetoric of the Iron Lady. Regardless of whether Peel, or Thatcher actually committed a betrayal of conservatism in favor of liberalism, the tension between conservatism and liberalism remains an essential element of the main identity and ideological divisions on the British political scene.
TORIES OR WHIGS? THE PROBLEM OF THE RELATIONSHIPS OF CONSERVATISM AND LIBERALISM IN BRITISH POLITICAL TRADITION
Keywords: conservatism; liberalism; Thatcherism; British political tradiction